2018
DOI: 10.1111/nyas.13589
|View full text |Cite
|
Sign up to set email alerts
|

Oral bisphosphonate use and age‐related macular degeneration: retrospective cohort and nested case–control study

Abstract: Our objective here was to determine whether oral bisphosphonate (BP) use is associated with the incidence of age-related macular degeneration (AMD). We performed a population-based study using electronic health records from UK primary care (Clinical Practice Research Datalink). A cohort of 13,974 hip fracture patients (1999-2013) was used to conduct (1) a propensity score-matched cohort analysis and (2) a nested case-control analysis. Hip fracture patients were aged ≥50 years without AMD diagnosis before hip f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…32 Other study showed that oral bisphosphonates use was not associated with an increased risk of ARMD, but the risk increased considerably with higher medication possession ratio. 3…”
Section: Bisphosphonates and Age-related Macular Degenerationmentioning
confidence: 99%
See 4 more Smart Citations
“…32 Other study showed that oral bisphosphonates use was not associated with an increased risk of ARMD, but the risk increased considerably with higher medication possession ratio. 3…”
Section: Bisphosphonates and Age-related Macular Degenerationmentioning
confidence: 99%
“…1,2 Bisphosphonates are the main therapeutic intervention for the treatment of confirmed diagnosis of osteoporosis in both men and postmenopausal women, with additional indications for other diseases. 3,[8][9][10][11][12][13][14][15] Bisphosphonates have been shown to induce improvement of bone mineral density, suppression of osseous turnover and a real time reduction of fracture risk and morbidity. 12 However, bisphosphonates have been associated with some rare and severe adverse effects, such as atypical femur fractures, 3,4,9,10,13 other atypical fractures, 16 osteonecrosis of the jaw (ONJ), 3,4,8,9,13,[17][18][19][20] an increased risk of aseptic osteonecrosis (AON), 8 atrial fibrillation, 4,9,10,13,21 esophageal and colon cancer, 4,9,10,22 bone and muscle pain, 4,9,13 irregular heartbeat, gastrointestinal intolerance, upper gastrointestinal (GI) adverse effects, acute phase reaction, hypocalcemia, impaired fracture healing, renal complications, electrolyte imbalance, and ocular inflammation.…”
Section: Bisphosphonates: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations